(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article presents a comparative analysis of the morpho-economic traits of the T-826 line belonging to Gossypium hirsutum L. with the standard varieties Namangan-77 and S-6524. The study was conducted in 2023 under the conditions of the Tashkent region based on phenological observations of 100 plants. According to the analysis results, the main stem height of the T-826 line was 114.8 cm, which was lower than that of Namangan-77 (117.5 cm) and S-6524 (118.1 cm). However, in terms of the number of fruiting branches, T-826 (12.3 branches) showed higher values compared to both standard varieties (11.7 and 11.0 branches, respectively). The T-826 line also demonstrated superiority in the number of locules per boll (4.70) compared with Namangan-77 (4.40) and S-6524 (4.61). In general, although the T-826 line exhibited a relatively shorter plant height, positive differences were observed in generative traits (yield components). The obtained results indicate that the T-826 line can be considered a promising source with high yield potential for use in cotton breeding programs.